New onset vasomotor symptoms but not musculoskeletal symptoms associate with clinical outcomes on extended adjuvant letrozole – Analyses from NCIC CTG MA.17. (June 2016) - Liedke, P.E.R.; Tu, D.; Shepherd, L.; Chavarri-Guerra, Y.; Pritchard, K.I.; Stearns, V.; Goss, P.E.
Abstract: Purpose: New onset symptoms on adjuvant aromatase inhibitors for hormone receptor positive early breast cancer may associate with clinical outcomes. We performed this exploratory analysis of the association of new onset musculoskeletal (MSK) and vasomotor (VM) symptoms with clinical outcomes in the NCIC CTG MA.17 trial 5 years of extended adjuvant endocrine therapy with letrozole after tamoxifen. Methods: Symptoms were collected at baseline, 1, 6, and every 12 months on study. Multivariate Cox Models adjusting for age, nodal status, duration of tamoxifen and prior chemotherapy were used to compare disease-free survival (DFS), distant disease-free survival (DDFS), and overall survival (OS) based on data collected before, and after, the unblinding between women with VM or MSK symptoms and those without. Results: Data post-unblinding showed new VM symptoms on extended letrozole significantly improved DFS and DDFS when occurring 1 month (DFS HR 0.52, 95% CI, 0.28–0.96; p = 0.04; DDFS HR 0.49, 95% CI, 0.24–0.99; p = 0.046) and 6 months (DFS HR 0.43, 95% CI, 0.24–0.78; p = 0.006; DDFS HR 0.44, 95% CI, 0.22–0.85; p = 0.02) after treatment initiation. Those with new VM symptoms at 12 months also had a significantly better DFS (HR 0.47, 95% CI 0.26, 0.84; P = 0.01) and a trend in improved DDFS. Only a trend to improved OS was found for those with VM symptoms 6 month after treatment. No significant improvement was found for those with new MSK symptoms at any time point or for any endpoint. Conclusions: New onset VM symptoms with extended letrozole may be useful in predicting treatment benefit. Highlights: New menopausal symptoms with AI adjuvant therapy might predict clinical benefit. We analyzed occurrence of new symptoms with extended letrozole and clinical benefit. New vasomotor symptoms were associated with improved outcomes on extended letrozole. No association was found for new musculoskeletal symptoms and outcomes.